Social normalisation: Using marketing to make green normal. Issue 1 (28th December 2013) - Rettie, Ruth; Burchell, Kevin; Barnham, Chris
ABSTRACT This paper proposes a novel environmental marketing approach in which the adoption of greener consumer behaviours is encouraged by repositioning them as normal. The research was undertaken in order to help explain the disappointing performance of green marketing initiatives. The methodology was qualitative, with focus groups and a wide range of stimulus materials. The study illuminates the ways in which consumers conceptualise and adopt pro‐environmental behaviours and highlights the importance of consumer ideas about what is normal. The research indicates that consumers are more likely to adopt behaviour and products that they think are normal and that what is regarded as normal changes over time. New activities and products that are initially seen as different, and as outside normal behaviour, can eventually become mainstream and accepted as normal, in a process of 'social normalisation'. As part of this process, other behaviours, which have been mainstream everyday ways of doing things, can become marginalised over time. The research suggests that companies and policy makers tend to position green marketing initiatives as targeting a green niche and that this inhibits social normalisation and mainstream adoption. Green marketing can potentially play an important role in the social normalisation of green practices and products by portraying these as normal and everyday instead of emphasizing their greenness. The study contributes to understanding of consumer behaviour and the adoption of more sustainable products and practices and identifies practical ways to improve green initiatives. Copyright © 2013 John Wiley & Sons, Ltd.